The Swan : A Novel - Cohee, Jim (Book collections on Project MUSE., 2011)
Ten-year-old Aaron Cooper has witnessed the death of his younger sister, Pookie, and the trauma has left him unwilling to speak. Aaron copes with life's challenges by disappearing into his own imagination, envisioning being captain of the Kon Tiki, driving his sled in the snowy Klondike, and tiger hunting in India. He is guarded by secret friends like deposed Hungarian Count Blurtz Shemshoian and Blurtz's wonder dog, Nipper, who protect him from the creature from the Black Lagoon -- who hides in Aaron's closet at night. The tales he constructs for himself, the real life stories he is witness to, and his mother's desperate efforts to bring her son back from the brink, all come to a head at an emotional family dinner. Set in Indianapolis in 1957, The Swan is a fictional memoir about enduring love and the weighty nature of mortality.